Epidemiological, clinical characteristics and prognostic factors analysis of adult patients with hemophagocytic lymphohistiocytosis in a Chinese hospital - Xie, Mingjun; Wang, Yaman; Wang, Min; Zhou, Jun; Xu, Hua-Guo (Frontiers in Immunology, 2025)
BackgroundHemophagocytic lymphohistiocytosis (HLH) is a rare and life-threatening syndrome characterized by immune dysregulation and excessive inflammation. Although diagnostic criteria and treatment protocols of HLH are well-established for pediatric populations, managing adult HLH remains challenging.MethodsWe conducted a single-center retrospective cohort study with adult HLH using data from the First Affiliated Hospital with Nanjing Medical University (January 2015–November 2023). Patient demographics, triggers, and outcomes were analyzed. Trends in case volume, diagnostics, treatments, and 30-day mortality were assessed using Sen’s slope estimator. To evaluate the COVID-19 pandemic’s impact, we compared pre-/post-January 2020 data. Logistic regression, Kaplan-Meier survival analysis and resource utilization analysis were applied in the analysis.ResultsAmong 711 HLH patients (71.1% aged 43–78 years), malignancy (45.9%) and infection (31.3%) were the predominant triggers. Cases showed a non-significant upward trend (peak increase: 103.6%; slope=2.458; p = 0.348), while 30-day mortality showed a non-significant downward trend (slope=-0.819; p = 0.402). Post-pandemic, infectious indicators (e.g., WBC) differed significantly (p<0.05), though trigger distribution was unchanged (p = 0.790). Malignancy-related HLH who received HLH-specific therapy was associated with a higher survival rate (77.7% vs. 34.1%–63.4%; p<0.001). A positive correlation between systemic corticosteroid administration and favorable clinical outcome in geriatric patient cohorts. (≥69 years; 70.7% -75.5% vs. 29.6%–42.9%; p<0.001). Mean length of hospital stay (LOS) was 21.4 ± 19.2 days.ConclusionDespite advancements in pediatric HLH, adult HLH mortality remains high, driven by diagnostic delays, comorbid complexity, and lack of standardized protocols. Future efforts must prioritize: (1) adult-specific biomarkers for early diagnosis, (2) trigger-tailored immunotherapies, and (3) multidisciplinary care pathways to address multisystem involvement.